Indian summer : the secret history of the end of an empire - Tunzelmann, Alex von (London : Simon & Schuster, 2007)
At midnight on August 15, 1947, 400 million people were liberated from the British Empire. With the loss of India, its greatest colony, Britain ceased to be a superpower. This defining moment was brought about by a handful of people: Jawaharlal Nehru, the fiery Indian prime minister; Mohammed Ali Jinnah, the leader of the new Islamic Republic of Pakistan; Mohandas Gandhi, the mystical figure who enthralled a nation; and Louis and Edwina Mountbatten, the glamorous but unlikely couple sent to get Britain out of India. Within hours, their dreams would turn to chaos, bloodshed, and war. Behind the scenes, a secret personal drama was also unfolding, as Edwina Mountbatten and Jawaharlal Nehru began a passionate love affair. Their romance developed alongside Cold War conspiracies, the beginning of a terrible conflict in Kashmir, and an epic sweep of events that saw one million people killed and ten million dispossessed.--From publisher description.
A tryst with destiny -- In their gratitude our best reward -- Mohan and Jawahar -- Civis britannicus sum -- Dreaming of the east -- Private lives -- We want no Caesars -- Power without responsibility -- A new theater -- Now or never -- Operation madhouse -- A barrel of gunpowder -- Lightning speed is much too slow -- A full basket of apples -- A rainbow in the sky -- Paradise on earth -- The battle for Delhi -- Kashmir -- Maybe not today, maybe not tomorrow -- A kiss good-bye -- Echoes.
Keywords: GEN; Statesmen -- Biography -- India; India -- Partition, 1947 -- History